Fisetin Lowers Streptococcus suis serotype 2 Pathogenicity in Mice by Inhibiting the Hemolytic Activity of Suilysin - Zhang, Yanyan; Zong, Bingbing; Wang, Xiangru; Zhu, Yongwei; Hu, Linlin; Li, Pei; Zhang, Anding; Chen, Huanchun; Liu, Manli; Tan, Chen (Frontiers in Microbiology, 2018)
Abstract Streptococcus suis serotype 2 is a serious zoonotic pathogen and has attracted worldwide attention since the first human case was reported in Denmark in 1968. Some virulence factors have been reported to be involved in the pathogenesis of the infection caused by Streptococcus suis serotype 2, and then novel strategies to identify some anti-virulence compounds which can effectively inhibit the pathogenic bacterial infection have recently been reported. Suilysin is an essential virulence factor for Streptococcus suis serotype 2 since it creates pores in the target cells membranes, which aids bacterial colonization. The important role of suilysin in the virulence of Streptococcus suis serotype 2 renders it an ideal target for designing novel anti-virulence therapeutics. We find that fisetin, as a natural flavonoid, is a potent antagonist against suilysin-mediated hemolysis. The aim of this study is to evaluate the effect of fisetin on the hemolytic activity of suilysin from Streptococcus suis serotype 2. Fisetin is found to significantly inhibit the hemolytic activity of suilysin. Within the range of effective concentrations, fisetin does not influence the growth of Streptococcus suis serotype 2 and the expression of suilysin protein. In vitro, fisetin effectively inhibits the death of macrophages (J774A.1 and RAW264.7) infected with Streptococcus suis serotype 2 by weakening intracellular bacterial multiplication. Animal model experiment shows that fisetin effectively improves the survival rate of animals infected with Streptococcus suis serotype 2. Our findings suggest that fisetin could be used as an antitoxin against suilysin and be developed into a promising therapeutic candidate for treating Streptococcus suis serotype 2 infection.